THE EFFECTIVENESS OF COLLECTION OF LAND AND BUILDING TAX IN REGIONAL REVENUE AGENCY (BAPENDA) MAKASSAR CITY - Indriati Amirullah; Nurasia Natsir; Husni Binti Salam; Zulkhaeriyah (International Journal of Economics and Management Research, 2022)
This is motivated by the importance of taxes for state revenues and increasing regional finances. To achieve this goal, the government carries out the effectiveness of tax collection to increase regional income. By implementing the effectiveness of tax collection, the government expects tax revenue to be more optimal and reach the targets that have been set previously. The purpose of this study was conducted to determine the effectiveness of land and building tax collection at the Makassar City Regional Revenue Service in supporting Makassar City's PAD and to find out the inhibiting factors and supporters of PBB collection at the Makassar City Revenue Service. To achieve the objectives of this study, the type of research used is descriptive qualitative, namely to provide a clear picture of the problems studied, interpret and explain data systematically at the Makassar City Revenue Service with a qualitative research approach, namely conducting interviews with respondents who contain questions regarding matters related to research. The results of the study show that the effectiveness of land and building tax collection at the Regional Revenue Service of Makassar City is good or effective. However, the effectiveness of the collection can be increased so that the goals of the organization, namely increasing tax revenue, can be fulfilled. Meanwhile, to measure the effectiveness of land and building tax collection, namely by looking at the level of taxpayer compliance as measured through the juridical aspect. consists of WP registration, SPT reporting, tax calculation and tax payment.